Hydrulic Study of Earthen Pitchers - Nirmale, Ajit; Kumar, Virendra; Kothari, Mahesh; Purohit, R C; Singhvi, B.S.M (Journal of Agricultural Engineering, 2007)
A simple, but efficient, technological device is clay pitcher, which entails creation of rural employment, savings of scarce water resources, maximizing yield and a reduction in irrigation frequency. For the practical application of pitcher irrigation there is need to have basic information and understanding of system which leads to design criteria for pitcher irrigation. The saturated hydraulic conductivity, Ks, of pitchers is considered the most important factor affecting the outflow rate from pitchers. A modified falling head method and a constant head method were used to measure the saturated hydraulic conductivity of eight pitchers selected from local producers in Udaipur. The two methods of measuring Ks were found accurate. However, procedure for falling head method was faster and simpler. Ks varied from 360.5 to 484.0 mm/day considering falling head method and from 398.6 to 574.4 mm/day in case of constant head method. While the conductance calculated was in the range of 13705837.54 to 17983403.85 mmÂ²/day by falling head method and by constant head method it was in the range 15640326.92 to 21082408.74 mmÂ²/day.